Analisis Kekuatan Genggaman, Kelentukan Bahu Dan Daya Tahan Otot Lengan Terhadap Pukulan Forehand Dalam Permainan Tenismeja - Sahabuddin Sahabuddin; Syahruddin Syahruddin; Arman Fadillah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims, among others, (1) to determine the contribution of grip strength to forehand strokes in table tennis, (2) to determine the contribution of shoulder flexibility to forehand strokes in table tennis, (3) to determine the contribution of arm muscle endurance to forehand strokes in the game. table tennis, and (4) to determine the contribution of grip strength, shoulder flexibility and arm muscle endurance to forehand strokes in table tennis. This research is a descriptive quantitative research type. The population of this study were all male students of SMA Negeri 4 Pare - Pare as many as 40 people. The data analysis technique used is correlation and regression analysis technique using the SPSS version 24.00 system at a significant level of 95% or 0.05. Based on the results of data analysis, this study concludes that: 1) grip strength has a contribution to the forehand stroke in the game of tennis by 79%, (2) the flexibility of the shoulder has a contribution to the forehand stroke in the game of tennis by 63.5%, (3) Arm muscle endurance contributes to forehand strokes in table tennis by 54.5%, (4) grip strength, shoulder flexibility and arm muscle endurance contributes to forehand strokes in table tennis by 80.8%..